KESELAMATAN KESEHATAN KERJA (K3), LINGKUNGAN KERJA DAN KOMPENSASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT. SUNAN RUBBER PALEMBANG - Pertiwi, Reni; Fitriah, Wani (Jurnal Ilmu Manajemen, 2015)
The influence of work Health and Safety (K3), work Enviroment and Compensation on Employees’ work Productivity in Production field at PT. Sunan Rubber Palembang. The problems of this study were whether or not there was any influence of work health and safety (K3) on the employees’ work productivity, whether or not there was any influence of work Enviroment on employees’ work productivity, and whether or not there was any influence of Compensation on employees’ work productivity in Production field at PT. Sunan Rubber Palembang. This study was associative. The variabels of the study were work health and safety (K3), work Enviroment, work Compensation and work productivity. The population of the study was all the employees at Production PT. Sunan Rubber Palembang which was 350 employees. However, the samples of the study were 120 employees of production field. The data of the study were primary and secondary data. Primary data were questionnaire and interview the employees of production field and secondary were the story of company, human resources, company’s organizational structures. The technique of collecting the data was questionnaries and interviews. The technique of analysing the data qualitative and quantitative using Structural Equation Modelling (SEM) with Lisrel 8.30 for windows. Based on SEM analysis showed that work health and safety (K3) has loading value 0.035 (standardized factor loading < 0,40), it meant that this variable has barely influenced on work productivity. Work Enviroment variable has loading value -0.097 (standardized factor loading < 0,40 ) showed this variabel negatively either influence on employees’ work productivity. Compensation variabel has influenced on work productivity with loading value 0,45 (standardized factor loading > 0,40) it could be concluded that the influence among work health and safety (K3), work Enviroment and work Compensation on employees’ work productivity with percentage of 21% ,while 79% has been influenced by another external factors.